A comparative assessment of the contribution of two different models for clearing invasive alien plants using grazing regimes in the Eastern Cape, South Africa. Issue 3 (2nd July 2020) - Morokong, T; Blignaut, JN
Abstract : Invasive alien plants (IAPs) compromise the productive capability of a land parcel from both an economic and a biodiversity perspective. Given the magnitude of degradation and the benefits of landscape-scale restoration, a unified approach among stakeholders is required to upscale restoration efforts. Seeking such an approach, we compare the efficiencies of two restoration and land use models for the period 2014–2016. Model A is characterised by both mechanical and bioturbation as methods to control the IAPs combined with short duration, high-density rotational grazing. Model B uses mechanical and chemical methods to control IAPs, as well as a mixed rotational rest grazing system. We found that Model B's unit cost was 47% higher than that of Model A (R13 747, compared with R9 327 ha −1 ). Model B is also less efficient with respect to the use of time and labour required to clear a hectare. We also note that seeking to simultaneously achieve dual objectives (e.g. ecological and social) using a single instrument, such as clearing IAPs, violates Tinbergen's Golden Rule in Public Finance. By seeking efficiency on a single objective, e.g. with respect to ecological indicators, restoration will yield more benefits and impact more people for longer.